Doing the Right Thing : How Colleges and Universities Can Undo Systemic Racism in Faculty Hiring - Gasman, Marybeth (Book collections on Project MUSE., 2022)
"An honest confrontation of systemic racism in faculty hiring-and what to do about itWhile colleges and universities have been lauded for increasing student diversity, these same institutions have failed to achieve any comparable diversity among their faculty. In 2017, of the nation's full-time, tenure-track and tenured faculty, only 3 percent each were Black men, Black women, Hispanic men, and Hispanic women. Only 6 percent were Asian/Pacific Islander men, 5 percent were Asian/Pacific Islander women, and 1 percent were American Indian/Alaska Native. Why are the numbers so abysmal? In Doing the Right Thing, Marybeth Gasman takes a hard, insightful look at the issues surrounding the recruitment and hiring of faculty of color. Relying on national data and interviews with provosts, deans, and department chairs from sixty major universities, Gasman documents the institutional forces stymieing faculty diversification, and she makes the case for how such deficiencies can and should be rectified.Even as institutions publicly champion inclusive excellence and the number of doctoral students of color increases, Gasman reveals the entrenched constraints contributing to the faculty status quo. Impediments to progress include the alleged trade-off between quality and diversity, the power of pedigree, the rigidity of academic pipelines, the failures of administrative leadership, the lack of accountability among administration and faculty, and the opacity and arbitrariness of the recruitment and hiring process. Gasman contends that leaders must acknowledge institutional failures of inclusion, pervasive systemic racism, and biases that restrict people of color from pursuing faculty careers.Recognizing that individuals from all backgrounds are essential to the creation and teaching of knowledge, Doing the Right Thing puts forth a concrete call for colleges and universities to take action and do better"--